IN IN -VITRO REGENERATION OF LASORA ( TION OF LASORA (Cordia myxa Cordia myxa Cordia myxa Roxb.) USING NODAL SEGMENTS USING NODAL SEGMENTS - MINAKSHI PADHI; NIRAJ MISHRA, S. P. SINGH, PRIYANKA SINGH (The Bioscan, 2018)
To develop a reliable protocol for in-vitro propagation of lasora, an experiment was conducted in Plant Tissue culture Laboratory, Department of Horticulture, Institute of Agricultural Sciences, Banaras Hindu University,varanasi during the year 2015-16. The explants were dipped in 50 mg/L citric acid + 100 mg/L ascorbic acid for 20 min to avoid explant browning. These Explants were cultured on medium consisting of different concentrations of benzyladenine (BAP) and á-naphthalene acetic acid (NAA) was used to culture the explants. The highest average number of shoots (5) and highest average length (3.75 cm) of shoot were shown on medium supplemented with 3.5 mg/L BAP + 0.07 mg/L NAA. There was no shoots proliferation in control (without growth regulators). IBA was used for rooting of proliferated shoots. The rooting medium fortified with IBA (2mg/L) was found beneficial for days to root initiation, number of roots and root length.